Genetic diversity of the Landim mozambicano goat - Cavele, A.; Pérez Pineda, E.; Fonseca, N.; Ramírez, J. L.; Verdecia, D.; Martínez, María A.; Delgado, J. V.; Barba, C. J.; Grizelj, J. (Cuban Journal of Agricultural Science, 2023)
With the purpose of determine the genetic diversity of the "Landim Mozambicano" goat, a panel of 33 microsatellites molecular markers were analyzed, selected and recommended by the “Comité de Expertos de la FAO” and the “Sociedad Internacional de Genética Animal” for diversity studies in sheep and goats species. Hair samples of 60 individuals from six Mozambique provinces (Manica, Tete, Sofala, Nampula, Gaza e Inhambane) were taken, which groups the highest number of animals from the breed. The ADN of the capillary bulb was extracted and amplified by PCR in the laboratorio de Biología Molecular del Animal Breeding Consulting, S.L, de la Universidad de Córdoba, España. Electophoresis in poliacrilamide gel was carried out to separate the obtaining fragments in an Automatic Sequencer ABI Prism® 377 XL (Applied Biosystems).The fragments analysis and genotyped was performed by the informatics programs Genescan and Genotyper 3.7 NT. It was determined: allele total per marker, expected and observed heterozygosities and Polymorphic Information Content. All the microsatellites were polymorphic, a total of 214 alleles with 6.4 as average per marker were found. From the analyzed panel a total of 29 were informative, 11 highly informative and 3 exceptionally informative for the breed. As main find, the heterozygosities reached values higher than 60 %. It is concluded that the microsatellites battery was adequate to study the breed, four of them can be excluded in future studies and the "Landim" goat is a breed with adequate genetic diversity. Key words: goats, markers, ADN, Mozambique.